The Implementation of Income Tax Imposition on Online Business Operators in Indonesia Based on Current Tax Regulations - Kusen, Moch.; Arifin, Samsul; Pakpahan, Novritsar Hasitongan; Sinambela, Ella Anastasya; Sulani (Journal of Social Science Studies, 2023)
The imposition of income tax on online business operators in Indonesia has emerged as a critical issue amidst the rapid growth of e-commerce and digital transactions. Existing tax regulations, including the Income Tax Law and Government Regulation on Electronic-Based Trading Systems, have established tax obligations for online entrepreneurs. However, their implementation continues to face challenges, particularly in identifying business actors and monitoring cross-border online transactions. This article examines the effectiveness of tax regulation enforcement in the online business sector and its implications for economic equity and fiscal stability. Strengthening oversight mechanisms and enhancing transparency are expected to foster a healthier business environment. The findings also offer recommendations for regulatory improvements and the development of a taxation system that is adaptive to digital technologies. More efficient implementation will contribute to achieving fiscal objectives and promoting sustainable growth in the digital economy.